Blood–brain barrier leakage and hemorrhagic transformation: The Reperfusion Injury in Ischemic StroKe (RISK) study. (8th July 2021) - Arba, Francesco; Piccardi, Benedetta; Palumbo, Vanessa; Biagini, Silvia; Galmozzi, Francesco; Iovene, Veronica; Giannini, Alessio; Testa, Giuseppe Dario; Sodero, Alessandro; Nesi, Mascia; Gadda, Davide; Moretti, Marco; et al.
Abstract: Background and purpose: In patients with acute ischemic stroke treated with reperfusion therapy we aimed to evaluate whether pretreatment blood–brain barrier (BBB) leakage is associated with subsequent hemorrhagic transformation (HT). Methods: We prospectively screened patients with acute ischemic stroke treated with intravenous thrombolysis and/or endovascular treatment. Before treatment, each patient received computed tomography (CT), CT angiography, and CT perfusion. We assessed pretreatment BBB leakage within the ischemic area using the volume transfer constant (K trans ) value. Our primary outcome was relevant HT, defined as hemorrhagic infarction type 2 or parenchymal hemorrhage type 1 or 2. We evaluated independent associations between BBB leakage and HT using logistic regression, adjusting for age, sex, baseline stroke severity, Alberta Stroke Program Early CT Score (ASPECTS) ≥ 6, treatment type, and onset‐to‐treatment time. Results: We enrolled 171 patients with available assessment of BBB leakage. The patients' mean (±SD) age was 75.5 (±11.8) years, 86 (50%) were men, and the median (interquartile range) National Institutes of Health Stroke Scale score was 18 (12–23). A total of 32 patients (18%) received intravenous thrombolysis, 102 (60%) underwent direct endovascular treatment, and 37 (22%) underwent both. Patients with relevant HT ( N  = 31;18%) had greater mean BBB leakage (K trans 0.77 vs. 0.60; p  = 0.027). After adjustment in the logistic regression model, we found that BBB leakage was associated both with a more than twofold risk of relevant HT (odds ratio [OR] 2.50; 95% confidence interval [CI] 1.03–6.03 per K trans point increase; OR 2.34; 95% CI 1.06–5.17 for K trans values > 0.63 [mean BBB leakage value]) and with symptomatic intracerebral hemorrhage (OR 4.30; 95% CI 1.13–13.77 per K trans point increase). Conclusion: Pretreatment BBB leakage before reperfusion therapy was associated with HT, and may help to identify patients at risk of HT. Abstract : We tested the hypothesis that blood–brain barrier (BBB) leakage is associated with subsequent hemorrhagic transformation in patients with ischemic stroke. We evaluated BBB leakage with computed tomography perfusion before any reperfusion therapy, and found that greater BBB leakage was associated with hemorrhagic transformation. This finding may help in the management of acute stroke patients and selection of patients for trials evaluating new reperfusion therapies.